Pengaruh Cita Rasa Dan Persepsi Harga Terhadap Keputusan Pembelian Kopi Arabika di Kecamatan Bastem - Desty; Nanda; Della Hendra; Andini Sudarmin; Nasruddin; Rudianto (JURNAL ILMIAH RESEARCH STUDENT, 2023)
This research aims to determine the simultaneous and partial influence of taste and price perception on purchasing decisions for Arabica coffee in Bastem sub-district. The type of research used is associative research with a quantitative approach. The population of this research is people who buy Arabica Coffee in Bastem District based on word of mouth information with a sample of 97 respondents taken randomly. Data obtained using a questionnaire is in the form of a Likert scale. From the results of the multiple regression estimation, it can be seen that taste and price simultaneously have a positive and significant effect on purchasing decisions in Bastem District. Partial taste does not have a significant effect on purchasing decisions in Bastem District. Price perception partially has a positive and significant effect on purchasing decisions in Bastem District.